Gas diffusion layer and preparation method and application thereof

By using a combination of porous nickel felt, a hydrophilic modifier and graphene oxide, a gas diffusion layer with high hydrophilicity and conductivity was prepared, which solved the problems of catalyst agglomeration and internal resistance, and improved the performance of the membrane electrode.

CN119663318APending Publication Date: 2025-03-21HUANENG YIMIN COAL POWER CO LTD +1

Patent Information

Application Number
CN202411717760.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, hydrophilic and hydrophobic improvement of the catalytic layer in the membrane electrode can easily cause the catalyst to agglomerate or dissolution, and the hydrophilic and hydrophobic improvement will lead to a greater internal resistance of the membrane electrode.

Method used

A porous nickel felt is used as the base material of the gas diffusion layer, and a coating liquid is obtained by mixing a hydrophilic modifier, solvent and graphene oxide. It is coated on the porous nickel felt, and the gas diffusion layer is prepared after drying.

Benefits of technology

The hydrophilicity and electrical conductivity of the gas diffusion layer are improved, the internal resistance is reduced, the cathode electrochemical reaction efficiency is enhanced, and the hydrogen exhaust can be facilitated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663318A_ABST
    Figure CN119663318A_ABST
Patent Text Reader

Abstract

The invention provides a gas diffusion layer and a preparation method and application thereof. The preparation method of the gas diffusion layer comprises the following steps: S1, providing a porous nickel felt which is made of nickel fibers; s2, mixing a hydrophilic modifier, a solvent and graphene oxide to obtain a coating liquid; and S3, the surface of one side of the porous nickel felt is coated with the coating liquid, and the gas diffusion layer is obtained after drying treatment. The porous nickel felt is adopted as a base material of the gas diffusion layer, and compared with traditional foamed nickel or a nickel net, the porous nickel felt can provide a pore channel structure and improve the mechanical strength of a base body at the same time, so that the effect of supporting the catalyst layer can be achieved, and hydrogen can be conveniently discharged. The introduction of the hydrophilic modifier can improve the hydrophilicity of the gas diffusion layer, thereby improving the electrochemical reaction efficiency of the cathode. The surface of the graphene oxide contains a large number of oxygen-containing functional groups, and the conductivity of the gas diffusion layer can be improved by introducing the graphene oxide into the coating liquid and coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a gas diffusion layer, a preparation method and application thereof. Background Art

[0002] Anion exchange membrane water electrolysis (AEMWE) technology is a new water electrolysis technology that uses anion exchange membrane as a diaphragm. It combines the advantages of low cost of alkaline water electrolysis technology and faster response speed and higher current density of proton exchange membrane water electrolysis (PEMWE) technology.

[0003] The membrane electrode is the core component of AEMWE technology, which consists of a gas diffusion layer, a catalyst layer and an anion exchange membrane. It is also the main place for producing hydrogen and oxygen. During the anion membrane (AEM) water electrolysis reaction, the reactant water molecules penetrate from the anode side through the anion exchange membrane to the cathode side, and the following reaction occurs: 2H2O+2e - →H2+2OH - Therefore, in the AEM water electrolysis technology, the cathode side needs to have high water absorption characteristics, while the anode side needs to have low water absorption characteristics. The following reaction occurs on the anode side: 2OH - →1 / 2O2+H2O+2e - .

[0004] The existing document (publication number CN116641086A) discloses a high-stability membrane electrode and its preparation method, and a water electrolyzer using the same, wherein the high-stability membrane electrode comprises an anode gas diffusion layer, an anode catalyst layer, an anion exchange membrane, a cathode catalyst layer, and a cathode gas diffusion layer stacked in sequence; wherein the anode catalyst layer is prepared by the following steps: nickel ferrite catalyst, polytetrafluoroethylene, anion exchange membrane ionomer and solvent are mixed and stirred evenly to obtain nickel ferrite catalyst slurry; the nickel ferrite catalyst slurry is coated on the anode gas diffusion layer, dried to obtain a membrane electrode intermediate, and the membrane electrode intermediate is kept in an inert gas at a holding temperature of 300 to 500°C for 5 to 60 minutes to obtain an anode catalyst layer. The document proposes to optimize the anode catalyst layer and add hydrophobic materials such as polytetrafluoroethylene to achieve the hydrophobic effect of the anode.

[0005] Existing document (publication number CN118563349A) discloses a water electrolysis membrane electrode and its preparation method, and a water electrolyzer using the same, wherein the water electrolysis membrane electrode comprises a cathode gas diffusion layer, a cathode catalyst layer, an anion exchange membrane, a hydrophobic anode catalyst layer, and an anode gas diffusion layer stacked in sequence; the preparation raw materials of the hydrophobic anode catalyst layer include an anode catalyst, a hydrophobic material, and an anode ionomer, and the anode catalyst: hydrophobic material: anode ionomer is calculated according to the mass ratio, and the porosity of the hydrophobic anode catalyst layer is 10-40%. In the document, a single-side water inlet mode on the anode side is designed, and then the anode catalyst layer is optimized by adding anode hydrophobic material polytetrafluoroethylene to achieve the effect of rapid drainage on the anode side, and carboxylated carbon nanotubes are added to the cathode to optimize the hydrophilic effect of the cathode catalyst layer. However, this is based on the fact that the cathode side does not directly inlet water, and the anode reactant water is transmitted to the cathode for reaction, resulting in an increase in ohmic resistance and an increase in activation overpotential.

[0006] The above existing technologies all perform hydrophilic-hydrophobic improvements on the catalytic layer, which can easily cause catalyst agglomeration or dissolution; moreover, the gas diffusion layer in the existing AEM electrolytic water tank is usually made of materials such as nickel mesh, which has a high hardness and an uneven surface, and can easily perforate the anion membrane and cause a membrane electrode short circuit.

[0007] On this basis, researching and developing a method for preparing a gas diffusion layer that can improve hydrophilicity without causing catalyst agglomeration or dissolution and can reduce internal resistance is of great significance for improving the performance of membrane electrodes. Summary of the invention

[0008] The main purpose of the present invention is to provide a gas diffusion layer, its preparation method and application, so as to solve the problem in the prior art that the hydrophilic-hydrophobic improvement of the catalytic layer in the membrane electrode easily causes catalyst agglomeration or dissolution, and the hydrophilic-hydrophobic improvement leads to a large internal resistance of the membrane electrode.

[0009] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a gas diffusion layer on one hand, which comprises: step S1, providing a porous nickel felt, wherein the material of the porous nickel felt is nickel fiber; step S2, mixing a hydrophilic modifier, a solvent and graphene oxide to obtain a coating liquid; step S3, coating the coating liquid on one side surface of the porous nickel felt, and obtaining a gas diffusion layer after drying.

[0010] Furthermore, the weight ratio of the hydrophilic modifier, the solvent and the graphene oxide is (5-8):(40-50):(1-3).

[0011] Furthermore, the loading amount of graphene oxide in the gas diffusion layer is 0.1-0.3 wt %.

[0012] Furthermore, the hydrophilic modifier is selected from one or more of the group consisting of sodium carboxymethyl cellulose, polyacrylic acid, polyacrylic acid peptide amine and polyvinyl alcohol; preferably, the weight average molecular weight of sodium carboxymethyl cellulose is 263.2-1316.

[0013] Furthermore, the solvent is selected from one or more of the group consisting of water, ethanol aqueous solution and ethylene glycol aqueous solution.

[0014] Furthermore, the atomic percentage of oxygen-containing functional groups in graphene oxide is 40 to 60 wt %.

[0015] Furthermore, step S2 includes: step S2-1, mixing a hydrophilic modifier with a solvent to obtain a dispersion; step S2-2, mixing the dispersion with graphene oxide, and obtaining a coating liquid after ultrasonic treatment.

[0016] Furthermore, the solid content of the dispersion is 12-22 wt %.

[0017] Furthermore, the mixing in step S2-1 is carried out under stirring conditions of 300 to 500 rpm, and the stirring time is 1 to 2 hours.

[0018] Furthermore, the temperature of the ultrasonic treatment is 0-5°C, and the time is 40-80 min.

[0019] Furthermore, the porosity of the porous nickel felt is 60-80%.

[0020] Furthermore, the average diameter of the nickel fiber is 10 to 30 μm.

[0021] Furthermore, the thickness of the porous nickel felt is 0.3-0.6 mm.

[0022] Furthermore, the coating process is performed by a slit coating method.

[0023] Furthermore, a coating machine is used for coating, the slit height is set to 0.4-0.8 mm, and the coating rate is set to 0.5-0.8 mm / s.

[0024] Furthermore, the coating amount of the coating liquid is 0.2 to 0.4 g / cm 2 .

[0025] Furthermore, the drying temperature is 50-70° C. and the drying time is 5-10 min.

[0026] In order to achieve the above-mentioned object, another aspect of the present invention further provides a gas diffusion layer, which is prepared by the above-mentioned preparation method provided in the present application.

[0027] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides an anion exchange membrane water electrolyzer, comprising a cathode electrode plate, a cathode gas diffusion layer, a CCM-type membrane electrode, an anode gas diffusion layer and an anode electrode plate stacked in sequence, the CCM-type membrane electrode comprising a cathode catalyst layer, an anion exchange membrane and an anode catalyst layer stacked in sequence, and the cathode catalyst layer is arranged between the cathode gas diffusion layer and the anion exchange membrane, and the anode catalyst layer is arranged between the anion exchange membrane and the anode gas diffusion layer. The above-mentioned gas diffusion layer is the above-mentioned gas diffusion layer provided in the present application.

[0028] The technical solution of the present invention is applied, and porous nickel felt is used as the matrix material of the gas diffusion layer. Compared with traditional nickel foam or nickel mesh, the mechanical strength of the matrix can be improved while providing a pore structure, so that the role of supporting the catalyst layer can be played, and the discharge of hydrogen can be facilitated. In the above-mentioned preparation method of the present application, a hydrophilic modifier, a solvent and graphene oxide are mixed to obtain a coating liquid, and then the coating liquid is coated on one side surface of the porous nickel felt. During the coating process, a part of the coating liquid penetrates into the porous nickel felt, and a part remains on the surface. After drying, the gas diffusion layer can be obtained. The introduction of a hydrophilic modifier can improve the hydrophilicity of the gas diffusion layer, thereby improving the efficiency of the cathode electrochemical reaction. The surface of graphene oxide contains a large number of oxygen-containing functional groups, such as hydroxyl, carboxyl, etc., and introducing it into the coating liquid and coating it can improve the conductivity of the gas diffusion layer. Moreover, compared with graphene (rGO), graphene oxide (GO) has a higher specific surface area and porosity, and the introduction of graphene oxide in the gas diffusion layer can further improve its conductivity.

[0029] In addition, the preparation method provided in the present application is simple and can be industrially produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0031] Figure 1 A schematic structural diagram of an anion exchange membrane water electrolyzer is shown.

[0032] The above drawings include the following reference numerals:

[0033] 10. Cathode electrode plate; 20. Cathode gas diffusion layer; 30. CCM membrane electrode; 40. Anode gas diffusion layer; 50. Anode electrode plate; 31. Cathode catalyst layer; 32. Anion exchange membrane; 33. Anode catalyst layer. DETAILED DESCRIPTION

[0034] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0035] As described in the background technology, the existing membrane electrode improvement method has the problem that the hydrophilic-hydrophobic improvement of the catalyst layer easily causes catalyst agglomeration or dissolution, and the hydrophilic-hydrophobic improvement leads to a large internal resistance of the membrane electrode. In order to solve the above technical problems, the first aspect of the present application provides a method for preparing a gas diffusion layer, which includes: step S1, providing a porous nickel felt, the material of the porous nickel felt is nickel fiber; step S2, mixing a hydrophilic modifier, a solvent and graphene oxide to obtain a coating liquid; step S3, coating the coating liquid on one side of the porous nickel felt, and obtaining a gas diffusion layer after drying.

[0036] Porous nickel felt is used as the matrix material of the gas diffusion layer. Compared with traditional nickel foam or nickel mesh, the mechanical strength of the matrix can be improved while providing a pore structure, so that the role of supporting the catalyst layer can be played, and the discharge of hydrogen can be facilitated. In the above-mentioned preparation method of the present application, a hydrophilic modifier, a solvent and graphene oxide are mixed to obtain a coating liquid, and then the coating liquid is coated on one side surface of the porous nickel felt. During the coating process, a part of the coating liquid penetrates into the porous nickel felt, and a part is left on the surface. After drying, the gas diffusion layer can be obtained. The introduction of a hydrophilic modifier can improve the hydrophilicity of the gas diffusion layer, thereby improving the efficiency of the cathode electrochemical reaction. The surface of graphene oxide contains a large amount of oxygen-containing functional groups, such as hydroxyl, carboxyl, etc., and introducing it into the coating liquid and coating it can improve the conductivity of the gas diffusion layer. Moreover, compared with graphene (rGO), graphene oxide (GO) has a higher specific surface area and porosity, and the introduction of graphene oxide in the gas diffusion layer can further improve its conductivity.

[0037] In addition, the preparation method provided in the present application is simple and can be industrially produced.

[0038] In a preferred embodiment, the weight ratio of the hydrophilic modifier, the solvent and the graphene oxide is (5-8):(40-50):(1-3). The weight ratio of the hydrophilic modifier, the solvent and the graphene oxide includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the hydrophilicity and conductivity of the gas diffusion layer, and is also beneficial to improving the dispersibility of the hydrophilic modifier and the graphene oxide, and the processability of the prepared coating liquid.

[0039] In a preferred embodiment, the loading amount of graphene oxide in the gas diffusion layer is 0.1-0.3 wt %. The loading amount of graphene oxide in the gas diffusion layer includes but is not limited to the above range, and limiting it within the above range is conducive to improving the conductivity of the gas diffusion layer.

[0040] In a preferred embodiment, the hydrophilic modifier includes but is not limited to one or more of the group consisting of sodium carboxymethyl cellulose, polyacrylic acid, polyacrylic acid peptide amine and polyvinyl alcohol. The above-mentioned hydrophilic modifier contains hydrophilic functional groups, such as hydroxyl and carboxyl groups, which is beneficial to improve the hydrophilicity of the gas diffusion layer. Moreover, the above-mentioned hydrophilic modifier has good solubility and film-forming properties, which is beneficial to coating processing. In addition, graphene oxide has a lamellar structure, and the above-mentioned hydrophilic modifier can also form a hydrogen bond grid between layers in graphene oxide, thereby affecting its interlayer spacing, improving the elastic modulus of the gas diffusion layer, and improving the mechanical properties of the gas diffusion layer itself.

[0041] In order to further improve the hydrophilicity of the gas diffusion layer and further improve the solubility and film-forming property of the hydrophilic modifier, preferably, the weight average molecular weight of sodium carboxymethyl cellulose is 263.2-1316.

[0042] The coating liquid generally contains a solvent component. In a preferred embodiment, the solvent includes, but is not limited to, one or more of the group consisting of water, ethanol aqueous solution, and ethylene glycol aqueous solution. Compared with other types, the use of the above types of solvents is conducive to improving the dispersibility of the hydrophilic modifier and graphene oxide, which is convenient for subsequent coating.

[0043] In order to further improve the hydrophilicity of the gas diffusion layer, preferably, the atomic percentage of oxygen-containing functional groups in the graphene oxide is 40 to 60 wt %.

[0044] In a preferred embodiment, step S2 includes: step S2-1, mixing a hydrophilic modifier with a solvent to obtain a dispersion; step S2-2, mixing the dispersion with graphene oxide, and obtaining a coating liquid after ultrasonic treatment. The above mixing method is conducive to improving the dispersibility of each raw material and facilitating improving the uniformity of the coating liquid.

[0045] In a preferred embodiment, the solid content of the dispersion is 12-22 wt %. The solid content of the dispersion includes but is not limited to the above range, and limiting it within the above range is conducive to improving the dispersibility of the hydrophilic modifier and facilitating subsequent mixing with graphene oxide.

[0046] In order to further improve the dispersibility of the hydrophilic modifier in the dispersion, preferably, the mixing in step S2-1 is carried out under a stirring condition of 300 to 500 rpm for 1 to 2 hours.

[0047] In a preferred embodiment, the temperature of the ultrasonic treatment is 0-5°C and the time is 40-80 minutes. The temperature and time of the ultrasonic treatment include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the dispersibility of graphene oxide and inhibiting the agglomeration of graphene oxide, thereby facilitating subsequent coating.

[0048] In a preferred embodiment, the porosity of the porous nickel felt is 60-80%. The porosity of the porous nickel felt includes but is not limited to the above range, and limiting the porosity within the above range is conducive to providing a transmission channel for hydrogen and facilitating the discharge of hydrogen.

[0049] In order to further provide a transmission channel for hydrogen and to improve the mechanical strength of the porous nickel felt as a matrix material, preferably, the average diameter of the nickel fiber is 10 to 30 μm.

[0050] In a preferred embodiment, the thickness of the porous nickel felt is 0.3-0.6 mm. The thickness of the porous nickel felt includes but is not limited to the above range, and limiting it within the above range is conducive to better playing its role in supporting the catalyst layer and providing a channel for hydrogen discharge.

[0051] In a preferred embodiment, the coating process is performed by a slit coating method. Compared with other coating methods, the slit coating method is easy to improve the coating efficiency, and the process is simple and easy to operate.

[0052] It should be noted that the slit height in the present application refers to the vertical distance between the end of the scraper in the coater and the porous nickel felt.

[0053] In a preferred embodiment, a coating machine is used for coating, and the slit height is set to 0.4-0.8 mm, and the coating rate is set to 0.5-0.8 mm / s. Compared with other ranges, limiting the slit height and coating rate within the above range is conducive to improving the thickness uniformity of the coated wet film, thereby facilitating the improvement of the surface smoothness of the gas diffusion layer and reducing the mechanical damage of the anion membrane to the gas diffusion layer such as perforation and puncture.

[0054] In order to further improve the hydrophilicity and conductivity of the gas diffusion layer and to further improve its surface smoothness, preferably, the coating amount of the coating liquid is 0.2 to 0.4 g / cm 2 .

[0055] In a preferred embodiment, the drying temperature is 50-70°C and the time is 5-10 minutes. The drying temperature and time include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the drying efficiency and drying effect of the coated wet film, thereby facilitating better play of the role of the hydrophilic modifier and graphene oxide, thereby improving the hydrophilicity and conductivity of the gas diffusion layer.

[0056] The second aspect of the present application provides a gas diffusion layer, which is prepared by the above-mentioned preparation method provided by the present application. The porous nickel felt is used as the base material of the gas diffusion layer. Compared with the traditional nickel foam or nickel mesh, it can improve the mechanical strength of the base while providing a pore structure, so that it can play a role in supporting the catalytic layer and facilitate the discharge of hydrogen. The introduction of a hydrophilic modifier in the gas diffusion layer can improve its hydrophilicity, thereby improving the efficiency of the cathode electrochemical reaction; the introduction of graphene oxide can improve the conductivity of the gas diffusion layer, and, compared with graphene (rGO), graphene oxide (GO) has a higher specific surface area and porosity, which can further improve its conductivity.

[0057] The third aspect of the present application provides an anion exchange membrane water electrolyzer, such as Figure 1 As shown, it includes a cathode plate 10, a cathode gas diffusion layer 20, a CCM membrane electrode 30, an anode gas diffusion layer 40 and an anode plate 50 stacked in sequence, and the CCM membrane electrode 30 includes a cathode catalyst layer 31, an anion exchange membrane 32 and an anode catalyst layer 33 stacked in sequence, and the cathode catalyst layer 31 is arranged between the cathode gas diffusion layer 20 and the anion exchange membrane 32, and the anode catalyst layer 33 is arranged between the anion exchange membrane 32 and the anode gas diffusion layer 40. The cathode gas diffusion layer 20 is the gas diffusion layer provided by the present application. The gas diffusion layer has good hydrophilicity, electrical conductivity and mechanical strength. The application of the gas diffusion layer in an anion exchange membrane water electrolyzer can significantly improve the efficiency of the cathode electrochemical reaction, thereby improving the efficiency of water electrolysis.

[0058] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0059] Example 1

[0060] A method for preparing a gas diffusion layer, comprising:

[0061] (1) preparing a porous nickel felt composed of nickel fibers, wherein the porous nickel felt has a thickness of 0.4 mm, a porosity of 80%, and an average diameter of the nickel fibers of 20 μm, cutting the porous nickel felt into a sheet-like porous nickel felt with a side length of 5 cm, first ultrasonically cleaning the felt with acetone for 30 min, then ultrasonically cleaning the felt with ethanol for 30 min, and finally repeatedly rinsing the felt with clean water for 5 times and drying the felt at 60° C. for 4 h, and then using the felt as a base material for later use;

[0062] (2) 5 g of sodium carboxymethyl cellulose having a weight average molecular weight of 790 was mixed with 50 g of water, and stirred at 500 rpm for 1 h to obtain a dispersion having a solid content of 10 wt %; the dispersion and 1 g of graphene oxide were ultrasonically treated in an ice bath for 1 h to obtain a coating solution; wherein the atomic percentage of oxygen-containing functional groups in the graphene oxide was 50 wt %;

[0063] (3) Using a coating machine, the coating liquid is coated on one side of a sheet-like porous nickel felt, wherein the slit height is set to 0.5 mm and the coating rate is set to 0.5 mm / s, to obtain a sheet-like porous nickel felt containing a wet film; and after drying it at 60° C. for 8 min, a gas diffusion layer is obtained.

[0064] Example 2

[0065] The difference from Example 1 is that the weight ratio of sodium carboxymethyl cellulose, water and graphene oxide is 5:40:1.

[0066] Example 3

[0067] The difference from Example 1 is that the weight ratio of sodium carboxymethyl cellulose, water and graphene oxide is 8:50:3.

[0068] Example 4

[0069] The difference from Example 1 is that the weight ratio of sodium carboxymethyl cellulose, water and graphene oxide is 10:55:5.

[0070] Example 5

[0071] The difference from Example 1 is that in step (2), the stirring speed when mixing sodium carboxymethyl cellulose and water is 300 rpm and the stirring time is 2 h.

[0072] Example 6

[0073] The difference from Example 1 is that the stirring time when sodium carboxymethyl cellulose and water are mixed in step (2) is 1 hour.

[0074] Example 7

[0075] The difference from Example 1 is that in step (2), the stirring speed when mixing sodium carboxymethyl cellulose and water is 800 rpm and the stirring time is 0.5 h.

[0076] Example 8

[0077] The difference from Example 1 is that the dispersion liquid and graphene oxide are ultrasonically treated at room temperature to obtain a coating liquid.

[0078] Example 9

[0079] The difference from Example 1 is that the porosity of the porous nickel felt is 60%.

[0080] Example 10

[0081] The difference from Example 1 is that the porosity of the porous nickel felt is 80%.

[0082] Embodiment 11

[0083] The difference from Example 1 is that the porosity of the porous nickel felt is 50%.

[0084] Example 12

[0085] The difference from Example 1 is that the average diameter of the nickel fibers is 10 μm.

[0086] Example 13

[0087] The difference from Example 1 is that the average diameter of the nickel fibers is 30 μm.

[0088] Embodiment 14

[0089] The difference from Example 1 is that the average diameter of the nickel fibers is 50 μm.

[0090] Embodiment 15

[0091] The difference from Example 1 is that the slit height is 0.4 mm and the coating rate is 0.8 mm / s.

[0092] Example 16

[0093] The difference from Example 1 is that the slit height is 0.8 mm and the coating rate is 0.5 mm / s.

[0094] Embodiment 17

[0095] The difference from Example 1 is that the slit height is 1.0 mm and the coating rate is 0.3 mm / s.

[0096] Embodiment 18

[0097] The difference from Example 1 is that the drying temperature is 90° C. and the drying time is 20 min.

[0098] Comparative Example 1

[0099] A pure nickel plain mesh with a wire diameter of 30 mesh and a thickness of 0.21 mm (purchased from Wanbo Wire Mesh) was used as the gas diffusion layer.

[0100] Comparative Example 2

[0101] The difference from Example 1 is that: in step (2), graphene oxide is not introduced, sodium carboxymethyl cellulose is mixed with water to obtain a 20 wt % dispersion and the subsequent coating is directly performed.

[0102] The electrolyzer assembly process includes: stacking the cathode plate 10, the cathode gas diffusion layer 20, the CCM membrane electrode 30, the anode gas diffusion layer 40 and the anode plate 50 in sequence for assembly, wherein the assembly pressure is 6N and the fixing bolts are tightened in a diagonal order. Among them, the cathode gas diffusion layer 20 is the above-mentioned gas diffusion layer provided in the embodiments and comparative examples of the present application, the CCM-type membrane electrode 30 has a stacked structure of cathode catalyst layer 31 / anion exchange membrane 32 / anode catalyst layer 33, and the cathode catalyst layer 31 is arranged on the side close to the cathode gas diffusion layer 20, and the anode catalyst layer 33 is arranged on the side close to the anode gas diffusion layer 40, the cathode catalyst layer 31 includes a Pt / C catalyst, the anion exchange membrane 32 is a commercial anion membrane, and its model is Fumasep FAA-3-50 (Germany FUMATech Company), the anode catalyst layer 33 includes an IrO2 catalyst, the anode gas diffusion layer 40 is a nickel fiber felt with a thickness of 0.25 mm, the cathode plate 10 is a stainless steel platinum-plated plate, and the anode plate 50 is a stainless steel platinum-plated plate.

[0103] The above electrolytic cell was subjected to high frequency impedance test, cell voltage test and cell voltage fluctuation test. The test results are shown in Table 1.

[0104] Table 1

[0105]

[0106] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0107] Porous nickel felt is used as the matrix material of the gas diffusion layer. Compared with traditional nickel foam or nickel mesh, the mechanical strength of the matrix can be improved while providing a pore structure, so that the role of supporting the catalyst layer can be played, and the discharge of hydrogen can be facilitated. In the above-mentioned preparation method of the present application, a hydrophilic modifier, a solvent and graphene oxide are mixed to obtain a coating liquid, and then the coating liquid is coated on one side surface of the porous nickel felt. During the coating process, a part of the coating liquid penetrates into the porous nickel felt, and a part is left on the surface. After drying, the gas diffusion layer can be obtained. The introduction of a hydrophilic modifier can improve the hydrophilicity of the gas diffusion layer, thereby improving the efficiency of the cathode electrochemical reaction. The surface of graphene oxide contains a large amount of oxygen-containing functional groups, such as hydroxyl, carboxyl, etc., and introducing it into the coating liquid and coating it can improve the conductivity of the gas diffusion layer. Moreover, compared with graphene (rGO), graphene oxide (GO) has a higher specific surface area and porosity, and the introduction of graphene oxide in the gas diffusion layer can further improve its conductivity.

[0108] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a gas diffusion layer, characterized in that: The preparation method of the gas diffusion layer comprises: Step S1, providing a porous nickel felt, wherein the material of the porous nickel felt is nickel fiber; Step S2, mixing a hydrophilic modifier, a solvent and graphene oxide to obtain a coating solution; Step S3, coating the coating liquid on one side surface of the porous nickel felt, and obtaining the gas diffusion layer after drying.

2. The method for preparing a gas diffusion layer according to claim 1, characterized in that: The weight ratio of the hydrophilic modifier, the solvent and the graphene oxide is (5-8):(40-50):(1-3); Preferably, the loading amount of the graphene oxide in the gas diffusion layer is 0.1-0.3 wt %.

3. The method for preparing a gas diffusion layer according to claim 1 or 2, characterized in that: The hydrophilic modifier is selected from one or more of the group consisting of sodium carboxymethyl cellulose, polyacrylic acid, polyacrylic acid peptide amine and polyvinyl alcohol; preferably, the weight average molecular weight of the sodium carboxymethyl cellulose is 263.2 to 1316; Preferably, the solvent is selected from one or more of the group consisting of water, ethanol aqueous solution and ethylene glycol aqueous solution; Preferably, the atomic percentage of oxygen-containing functional groups in the graphene oxide is 40 to 60 wt %.

4. The method for preparing a gas diffusion layer according to any one of claims 1 to 3, characterized in that: The step S2 comprises: Step S2-1, mixing the hydrophilic modifier with the solvent to obtain a dispersion; Step S2-2, mixing the dispersion liquid with the graphene oxide, and obtaining the coating liquid after ultrasonic treatment.

5. The method for preparing a gas diffusion layer according to claim 4, characterized in that: The solid content of the dispersion is 12 to 22 wt %; Preferably, the mixing in step S2-1 is performed under stirring conditions of 300 to 500 rpm for 1 to 2 hours; Preferably, the temperature of the ultrasonic treatment is 0-5°C and the time is 40-80 min.

6. The method for preparing a gas diffusion layer according to any one of claims 1 to 5, characterized in that: The porosity of the porous nickel felt is 60-80%; Preferably, the average diameter of the nickel fiber is 10 to 30 μm; Preferably, the thickness of the porous nickel felt is 0.3-0.6 mm.

7. The method for preparing a gas diffusion layer according to claim 6, characterized in that: The coating process is carried out by a slot coating method; Preferably, the coating is performed using a coating machine, the slit height is set to 0.4-0.8 mm, and the coating rate is set to 0.5-0.8 mm / s; Preferably, the coating amount of the coating liquid is 0.2 to 0.4 g / cm 2 .

8. The method for preparing a gas diffusion layer according to claim 7, characterized in that: The drying process is carried out at a temperature of 50 to 70° C. and for a time of 5 to 10 minutes.

9. A gas diffusion layer, characterized in that: The gas diffusion layer is prepared by the preparation method according to any one of claims 1 to 8.

10. An anion exchange membrane water electrolyzer, comprising a cathode plate (10), a cathode gas diffusion layer (20), a CCM membrane electrode (30), an anode gas diffusion layer (40) and an anode plate (50) stacked in sequence, wherein the CCM membrane electrode (30) comprises a cathode catalyst layer (31), an anion exchange membrane (32) and an anode catalyst layer (33) stacked in sequence, and the cathode catalyst layer (31) is arranged between the cathode gas diffusion layer (20) and the anion exchange membrane (32), and the anode catalyst layer (33) is arranged between the anion exchange membrane (32) and the anode gas diffusion layer (40), characterized in that: The cathode gas diffusion layer (20) is the gas diffusion layer according to claim 9.

Citation Information

Patent Citations

  • High-stability membrane electrode and preparation method thereof, and water electrolyser applying high-stability membrane electrode

    CN116641086A

  • Water electrolysis membrane electrode, preparation method thereof and water electrolyzer applying water electrolysis membrane electrode

    CN118563349A

Cited By

  • Electrolytic bath air chamber for electrolyzing water and alkaline electrolytic bath

    CN120119273A

  • Water electrolysis membrane electrode, method for preparing the same, and water electrolyzer applying the same

    EP4656772A1